The use of Anagram Game to Improve Vocabulary at the Second Grade Student of SD IT ULIL ALBAB KAMAL - Wahyudi, Mohammad; Wijaya, Mohammad (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Speaking is the art of communicating in social situations so that people compete to learn languages ​​because this is an interesting goal for them to achieve. Communicating using English is very popular in the current era of globalization. English has many benefits for increasing your chances of making friends with other people from various countries and for getting a job abroad. Many schools from elementary school to university level have English learning materials. In this case, the research took place at SD IT Ulil Albab Kamal and focused on vocabulary, because the students' vocabulary was lacking so that they were not fluent in speaking English and did not have the courage to speak. The researcher also concluded questions that focus on the problem that occurred, namely: 1. How does the Second Grade Students of SD IT Ulil Albab Kamal improve vocabulary through anagram game? 2. How do the students respond toward the use of anagram game in the class? With this problem, researchers introduced the Anagram game and the methodology by using Descriptive Qualitative Method. Anagram game is a brain-teasing puzzle game, where players have to change one word into another word by rearranging the letters. This game is very good for improving vocabulary skills and prolonging memory for new words in English. Researchers used two instruments, namely observation and interviews. From the instruments used in collecting data in the field, producing conclusions by using the Anagram game, the Second Grade Students at SD IT Ulil Albab Kamal can understand the meaning of words when communicating by using English